Potensi Taman Argo Wisata Dibekasi Lokalisasi Kedung Banteng Menuju Kemandirian Ekonomi Di Desa Kedung Banteng Kecamatan Sukorejo Ponorogo - Alfajri, Ahmad Mahfud; Wahidah, Maulida Agustina Hidayatul; Fikriawan, Suad (Institut Agama Islam Sunan Giri Ponorogo, 2024)
Ponorogo Regency has a variety of natural beauty that can be found. Moreover, Ponorogo has various sectors that can boost regional foreign exchange. One of them is the tourism sector which is a source of regional income. Tourism development is currently starting to become one of the leading programs in regional development. The tourism development is expected to be able to contribute to the receipt of Regional Original Revenue (PAD) and create jobs in the region. Ponorogo Regency has potential and interesting natural resources to be developed as tourist destinations such as hot springs, historical relics, and mountain and hilly areas. This research aims to formulate a community-based tourism development model in Ponorogo Regency, especially in the Kedung Banteng Ex-Localization area. The method used is a qualitative method involving the village head and the community around the Ex-Localization, with in-depth interview techniques. The results of this study indicate the existence of a proposed tourism development model using a community development approach. Tourism development in the Kedung Banteng Ex-Localization area is basically a portrait of efforts to develop the tourism sector in Ponorogo Regency, especially in Kedung Banteng village, Sukorejo sub-district.